Aged Plastic Leaching of Dissolved Organic Matter Is Two Orders of Magnitude Higher Than Virgin Plastic Leading to a Strong Uplift in Marine Microbial Activity - Romera-Castillo, Cristina; Birnstiel, Stéphanie; Álvarez-Salgado, Xosé Antón; Sebastián, Marta (Frontiers in Marine Science, 2022)
Plastic debris reaching the ocean is exponentially increasing in parallel with plastic production. Once into seawater, plastic starts to leach organic compounds that are presumably additives and plastic oligomers, and that process is enhanced by solar radiation. From previous studies with virgin plastic, it has been estimated that up to 23,600 metric tons of dissolved organic carbon (DOC) can be released into seawater every year from all the plastic entering the ocean. However, most plastic found in the ocean has been aged through weathering and sunlight radiation, which could result in enhanced leaching. Despite this, dissolved organic matter (DOM) leaching from aged plastic and the effect on microbial communities and their activity has never been explored. Here we studied DOM leaching by aged plastic collected from a sand beach and how it compares with that from virgin plastic. After characterizing the DOM leached from plastic through fluorescence techniques, we also explored the bioavailability of the DOM leached and its fluorescent fraction through biodegradation experiments. Finally, we determined single cell activities of the prokaryotic community growing on the plastic leachates. We found that the release of DOC by aged plastic was two order of magnitude higher than that leached by virgin new plastic. Extrapolating that into the ocean and assuming that most of the plastic arriving there is not new, we estimated that up to 57,000 metric tons of DOC can be released by plastic debris every year. A fraction of the DOM released by plastic was fluorescent (FDOM), especially in the protein-like region, and bioavailable to microbial uptake, as it is also shown by the increase in the single cell activities of the bacteria growing on the leachates. Since most plastics in the ocean have been exposed to sunlight radiation provoking aging, our results unveil that the amount of carbon released by plastics is much higher than hitherto recognized, and thus will have a stronger impact in the oceanic carbon cycle and in marine ecosystems.